The Human Oocyte Preservation Experience (HOPE) a phase IV, prospective, multicenter, observational oocyte cryopreservation registry - Ezcurra Diego; Rangnow Jennifer; Craig Maryellen; Schertz Joan (BMC, 2009)
Abstract Background It has been recommended by the American Society of Clinical Oncology and the American Society of Reproductive Medicine that options to preserve fertility be presented at the outset of treatment for cancer. This recommendation may have arisen, in part, to the increasing survival of patients with cancer and the realization that certain forms of cancer treatment can lead to infertility. One option for these patients, particularly those with ethical or religious objections to freezing embryos is oocyte cryopreservation. However universal acceptance of these procedures has yet to be established, most likely due to a poor history of success and concerns that there has yet to be a comprehensive approach to evaluating these techniques. In light of this, a registry of patients undergoing oocyte cryopreservation, called the HOPE registry, is being implemented. Discussion The intent of the HOPE Registry is to enroll approximately 400 women of reproductive age who will undergo thawing/warming of oocytes and subsequent transfer. Data from the patients enrolled will be collected via a uniform, standardized form and will document important parameters such as demographics, laboratory procedures and outcomes, including following the outcomes of babies born for one year after birth. The results of the registry will be published on a yearly basis. Summary A patient registry has been established in order to systematically document the techniques and outcomes of oocyte cryopreservation procedures. The results will be published in order to provide a widely accessible resource that will allow patients who are considering these procedures validated information in order to make informed decisions as to how their treatment will proceed.